The Fundamental Secondary Instability of the Primary Mack Mode in Hypersonic Boundary Layers on Flat Plates (Advances in Applied Mathematics and Mechanics, 2019)
The secondary instability was investigated in high-speed boundary layers over flat plates by numerical methodology. The numerical simulation suggests that the main streaky structures in 2D hypersonic boundary transition process are resulted from the secondary instability theory caused by the primary 2D Mack mode. The secondary instability analysis found that a new family called fundamental family of solutions was found which is the least stable secondary instability when the amplitude of the primary mode instability reaches a threshold value. It is helpful for us to understand the fundamental breakdown in hypersonic boundary layers.